Utilization of Digital Media in Arabic Language Learning at Madrasah Aliyah: A Descriptive Qualitative Study - Agnes Shofinatulhusna; Dadan Nugraha; Miftahul Hidayat; Yesa Amelia (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to provide a comprehensive description of the utilization of various forms of digital media in Arabic language learning at Madrasah Aliyah, particularly in supporting the mastery of language skills and improving the quality of the learning process. A descriptive qualitative approach was employed, as it enables the researcher to observe phenomena in depth within their natural learning context. Data were collected through direct observation of learning activities, in-depth interviews with Arabic language teachers, students, and the madrasah principal, as well as documentation analysis of learning tools, digital materials, and institutional policies. These data were supplemented with relevant literature to strengthen the conceptual understanding. The data analysis process followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, and was validated through source and method triangulation. The findings indicate that various digital media, such as interactive PowerPoint presentations, audiovisual materials (instructional videos and animations), mobile applications for vocabulary and language exercises, Learning Management Systems (LMS), online quiz platforms, and the use of social media as a space for language practice, can enhance students’ motivation, interaction, and learning autonomy. These media not only enrich the learning experience but also provide opportunities for students to practice Arabic more flexibly and in alignment with their individual learning styles.